2019
DOI: 10.17547/kjsr.2019.27.3.268
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Work-Life Balance on Job Satisfaction and Turnover Intention of Hospital Nurses: Compared to Female Wage Workers

Abstract: This article is based on a part of the first author's doctoral dissertation from University.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
2
5
0
1
Order By: Relevance
“…The nurse participants also stated that they quit work because sick and personal leaves were not sufficiently guaranteed or because of work–life challenges they faced owing to tight work shift schedules. This was similar to results in a previous South Korean study (Son & Jung, 2019) that indicated nurses' work–life balance and job satisfaction were significantly lower and their intention to leave was 20 times higher than that of non‐nursing female wage earners. It is difficult for nurses to balance work and life because they are not provided with adequate resources to buffer job demands such as inflexible shift work schedule and mandatory night duty.…”
Section: Discussionsupporting
confidence: 90%
“…The nurse participants also stated that they quit work because sick and personal leaves were not sufficiently guaranteed or because of work–life challenges they faced owing to tight work shift schedules. This was similar to results in a previous South Korean study (Son & Jung, 2019) that indicated nurses' work–life balance and job satisfaction were significantly lower and their intention to leave was 20 times higher than that of non‐nursing female wage earners. It is difficult for nurses to balance work and life because they are not provided with adequate resources to buffer job demands such as inflexible shift work schedule and mandatory night duty.…”
Section: Discussionsupporting
confidence: 90%
“…The level of stress was measured using seven items each having a 4-point Likert scale. One item with a lower factor loading was excluded, as in the approach used by Son and Jung (2019). One of included items is "I don't have anyone to talk with about my serious problem."…”
Section: Methodsmentioning
confidence: 99%
“…Women's increasing participation in economic activities and the growing social awareness of quality of life have been accompanied by an increasing interest in work-life balance among women. The popular conceptualization of work-life balance has recently changed to emphasize the balance between an individual's entire work and non-work life, rather than solely focusing on the balance between work and family life [1]. Issues around work-life balance and imbalance can apply to both men and women, but familial pressure related to childbirth and child rearing is traditionally higher for women, which increases the burden of work-life imbalance on women [2].…”
Section: Introductionmentioning
confidence: 99%
“…Work-life imbalance has a negative effect on an individual's physical and psychological health [1]. A study by Camerino et al [3] found that work-life conflict had a significant association with presenteeism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation